PERAN ORANG TUA SEBAGAI PENDIDIK IMAN ANAK YANG PERTAMA DAN UTAMA DALAM MASA PANDEMI COVID-19 DI KOMUNITAS BRAYAT MINULYA - Damayanti, Adelina; Permana, Natalis Sukma (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2022)
Parents are persons who have a major role in educating the child's faith. Faith education needs to be given to children to grow Christian values and goodness in children. The Covid-19 pandemic situation has an impact on no more child faith formation in the Church. Child faith development has become parent-centered as the first and foremost child faith educator during the Covid-19 pandemic. The purpose of this study is to determine the role of parents, the challenges of educating children's faith during a pandemic, and the efforts made by parents in educating children's faith during a Pandemic. This research uses a descriptive qualitative approach. Data analysis techniques use structured interview techniques in the Brayat Minulya community. The informants in this study were parents who had children aged 5-12 years. The informants in this study were six (6) people. The results showed that informants knew enough about their role as parents in educating children's faith during the pandemic. Faith education can be done through parental example and teaching about spirituality. The challenges faced by parents in educating children's faith during the pandemic have become a new awareness for parents of their duties and responsibilities as first and foremost faith educators.